1999
DOI: 10.1108/02640479910329626
|View full text |Cite
|
Sign up to set email alerts
|

Access versus holdings: document delivery realities

Abstract: The access versus holdings debate has been one of the 'hot topics' within the information world for some time, and the performance of document delivery services is an integral part of the discussion. This article focuses on work currently being undertaken at the University of Liverpool to investigate and evaluate existing and future document supply services. Reference is made to related literature, the background to the pilot projects is explained, and the criteria utilised for the inclusion of services are pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1999
1999
2005
2005

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Yet a study at the University of Liverpool compared six services and concluded that although the BL still provided a fast reliable service with the greatest breadth of journal coverage, its failure to deliver on sophisticated interfaces which the new technology offered was a source of concern, as more limited services were easier to use. Nevertheless for a multi-faculty HE institution it was still the best option -but now with BIDS and UnCover as serious rivals (Boyle and Davies, 1999).…”
Section: Electronic Document Delivery and The Follett Reportmentioning
confidence: 99%
“…Yet a study at the University of Liverpool compared six services and concluded that although the BL still provided a fast reliable service with the greatest breadth of journal coverage, its failure to deliver on sophisticated interfaces which the new technology offered was a source of concern, as more limited services were easier to use. Nevertheless for a multi-faculty HE institution it was still the best option -but now with BIDS and UnCover as serious rivals (Boyle and Davies, 1999).…”
Section: Electronic Document Delivery and The Follett Reportmentioning
confidence: 99%
“…Traditional thinking has focussed on gaining the most effective use of funding to provide as many resources and access services as possible (e.g. Boyle and Davies, 1999). There has been an implicit assumption that the user will be able to retrieve successfully if the resourcing is suitably managed.…”
Section: Implications For Information Services Of the Futurementioning
confidence: 99%
“…The access versus ownership debate continues and the following articles explore the various issues surrounding this discussion. Boyle and Davies (1999) look at existing and future document supply services which are being investigated and evaluated by the University of Liverpool. Preliminary results of…”
Section: Access Versus Ownershipmentioning
confidence: 99%